Technological Capital, Liquidity, and Board Size: Impact on Firm Value - Ingkak Chintya Wangsih; Rosidawaty; Zulfikar Ikhsan Pane; Shitny Dwi Istiasih (www.amertainstitute.com, 2025)
This study explores the impact of technological capital, the current ratio, and the board of commissioners on the firm value of companies listed on the jakarta islamic index (jii) over the period from 2019 to 2023. A total of 75 annual reports were selected using purposive sampling. A quantitative research design is employed, using panel data from 16 companies selected through purposive sampling based on specific criteria such as availability of consistent financial reports, financial stability, and membership in the jii. The study uses technological capital disclosure, the current ratio, and the size of the board of commissioners as independent variables, with firm value, measured by the price to book value (pbv) ratio, as the dependent variable. Data are analyzed using eviews version 10. The findings reveal significant relationships between technological capital disclosure and firm value, underscoring the importance of technological adaptation and the technological educational background of the board of directors. This study contributes to understanding the dynamics of technology-driven strategies and governance in enhancing firm value in the context of indonesian islamic capital markets.